Study Identification of Some Species of Fish Using the Partial Fragment of Mitochondrial Cytochrome Oxidase Subunit-1Gene (COI) in Danau Panggang, South Borneo - Tuah Nanda Merlia Wulandari; Aroef Hukmanan Rais (Department of Aquaculture, 2021)
Danau Panggang is a unique habitat for fish species used for food and economic purposes that live in it. This study aims to identify several important and endangered fish species in Danau Panggang using the DNA sequence method and water quality in Danau Panggang. The DNA sequence was then aligned with the RefSeq from the GenBank data library by using the BLAST program of NCBI to find the closest identity associated with several types of fish samples being analyzed. The sequence analysis of the DNA show that some fish species analyzed have specific identifications :Trichopodus pectoralis, Phalacronotus apogon, Belodontichthys dinema, Anabas testudineus, and Leptobarbus hoevenii. Based on the results of the phylogenetic tree, it is also found that the relationship between fish taxons in flooded swamps of Danau Panggang is close to one another.